Pengaruh Skeptisme Profesional, Pengalaman Kerja dan Time Budget Pressure terhadap Kualitas Audit - Sambo, Eva Marin; Sufiati, Sufiati; Livia Edyson (Al-Buhuts, 2025)
This study aims to determine whether the influence of professional skepticism, work experience and time budget pressure on audit quality at public accounting firm in Makassar city. Data collection using primary data obtained from a questionnaire using saturated sample technique. The population is all auditors who work at the Public Accounting Firm in Makassar, totaling 32 auditors and all of them are used as samples. The analytical method used is multiple linear analysis. Based on the results of this study, it shows that professional skepticism and work experience have no effect on audit quality at public accounting firms in Makassar, while time budget pressure has a significant positive effect on audit quality at public accounting firms in Makassar